Sound Symbolism in Foreign Language Phonological Acquisition - Wrembel, Magdalena (Research in Language, 2010)
The paper aims at investigating the idea of a symbolic nature of sounds and its implications for in the acquisition of foreign language phonology. Firstly, it will present an overview of universal trends in phonetic symbolism, i.e. non-arbitrary representations of a phoneme by specific semantic criteria. Secondly, the results of a preliminary study on different manifestations of sound symbolism including emotionally-loaded representations of phonemes and other synaesthetic associations shall be discussed. Finally, practical pedagogical implications of sound symbolism will be explored and a number of innovative classroom activities involving sound symbolic associations will be presented.